Immunomodulatory Effects of Perioperative Dexmedetomidine in Ovarian Cancer: An In Vitro and Xenograft Mouse Model Study - Shin, Seokyung; Kim, Ki Jun; Hwang, Hye Jeong; Noh, Sewon; Oh, Ju Eun; Yoo, Young-Chul (Frontiers in Oncology, 2021)
Background The surgical stress response (SSR) causes immunosuppression which may cause residual tumor growth and micrometastasis after cancer surgery. We investigated whether dexmedetomidine affects cancer cell behavior and immune function in an ovarian cancer xenograft mouse model. Methods The effect of dexmedetomidine on cell viability and cell cycle was assessed using SK-OV-3 cells at drug concentrations of 0.5, 0.1, 5, and 10 µg mL-1. BALB/c nude mice were used for the ovarian cancer model with the Dexmedetomidine group (n=6) undergoing surgery with dexmedetomidine infusion and the Control group (n=6) with saline infusion for 4 weeks. Natural killer (NK) cell activity, serum proinflammatory cytokines, and cortisol were measured at predetermined time points and tumor burden was assessed 4 weeks after surgery. Results Dexmedetomidine had no effect on cell viability or cell cycle. Following a sharp decrease on postoperative day (POD) 1, NK cell activity recovered faster in the Dexmedetomidine group with significant difference vs. the Control group on POD 3 (P=0.028). In the Dexmedetomidine group, cortisol levels were lower on POD 3 (P=0.004) and TNF-α levels were lower at 4 weeks after surgery (P<0.001) compared to the Control group. The Dexmedetomidine group showed lower tumor burden at 4 weeks vs. the Control group as observed by both tumor weight (P<0.001) and the in vivo imaging system (P=0.03). Conclusions Dexmedetomidine infusion may improve ovarian cancer surgery outcome by suppressing the SSR and stress mediator release. Further studies are needed to elucidate the mechanisms by which dexmedetomidine acts on cancer and immune cells.